Building Trust or Masking Reality? The Effects of Brand Image, Greenwashing, and Influencer Marketing on Sustainable Buying Behavior in Indonesia Skincare Product - Yudistira, Alya Daywa; Aminah, Siti; Sholihah, Dewi Deniaty (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the influence of brand image, greenwashing, and influencer marketing on green purchase intention for Somethinc skincare products in Surabaya. The research addresses the issue of consumers' limited understanding of green marketing practices and their impact on the intention to purchase environmentally friendly products, particularly among local brands. This quantitative research employs a descriptive approach. Data were collected through questionnaires distributed to 128 respondents selected using purposive sampling, and analyzed using Partial Least Square (PLS) with the SmartPLS software. The results show that brand image has a significant positive effect on green purchase intention, with a coefficient value of 0.412 and a p-value <0.05. Greenwashing has a negative but not significant effect (coefficient -0.087; p-value > 0.05), while influencer marketing has a positive but not significant effect (coefficient 0.143; p-value > 0.05). These findings indicate that a positive perception of brand image is the main factor driving consumers' intention to purchase environmentally friendly skincare products, whereas the effects of greenwashing and influencer marketing are not statistically significant. The implications of this study highlight the importance of strengthening brand image in sustainable marketing strategies for the local skincare industry, amid increasing consumer awareness of environmental issues.